Study of a Center Pipe Oscillating Column Wave Energy Converter Combined with a Triboelectric Nanogenerator Device - Yan Huang; Shaohui Yang; Jianyu Fan; Zhichang Du; Beichen Lin; Yongqiang Tu; Lei Pan (Journal of Marine Science and Engineering, 2024)
Wave energy is one of the most widely distributed and abundant energies in the ocean, and its conversion technology has been broadly researched. In this paper, a structure that combines a traditional center pipe oscillating water column and a triboelectric nanogenerator is proposed. Firstly, the structural characteristics and geometric parameters of the device are designed. The working process of the device is introduced, the motion equation of the device is established, and the power generation principle of the triboelectric nanogenerator is deduced and analyzed theoretically. Secondly, hydrodynamic modeling and simulation are carried out, the influence of the bottom shape of the main floating body and the structural parameters of the sag plate on the hydrodynamic force of the device is analyzed, and an electric field simulation of the generation process of the friction nanogenerator is carried out. Finally, experiments involving the wave water tank of the proposed device are conducted, including charging the capacitor of the device under different wave conditions and directly lighting the LED lamp. The performance of the proposed device under different wave conditions is discussed. According to the test results, the feasibility of the proposed device for wave energy conversion is confirmed.